An Estimate of Unidentified and Total U.S. Coronavirus Cases by State on April 21, 2020 (2020)
I use data on cumulative tests, positive tests, and deaths for the coronavirus in South Korea and the U.S. lower-48 states during April 2020 to estimate the extent of infection and the unidentified share of the infected population in each state and in the U.S. as a whole on April 21, 2020. I find that 3.8 million people, or 1.2% of the population, have been infected in the U.S., with rates of infection that range from 0.1% in more rural states to 7.0% in New York state. I estimate that only 20% of all U.S. cases have been identified through testing. The unidentified share of total cases ranges from 61% to 83% across the states. I estimate that 38% of all cases are asymptomatic, which is consistent with the high shares of unidentified cases.